Here's the question you clicked on:
JessNicole
x+y=4 2x-y=5 What is the solution to this system?
use elimination method
add down using elimination method
add solve for x then solve for y I think it will be easier
multiply both side of x+y=4 by 5 and multiply both side of 2x-y=5 by 4
I think adding two equation will give you in x terms only... no ned to go in a roundabout way
Thank you SO MUCH! all of you @gerryliyana @Rosh007 @Mr.Me I appreciate 100% :p
welcome..so u got it... O glad..
Is the answer suppose to be a decimal tho??
because i got -0.3333333333.. etc.
what did u get it??
by using the elimination method ... Oh okay @gerryliyana then plug that in to x in x+y=4 ?
yes... first you nd to eliminate one variable... sinc there are two equations and two unknowns.. it would is possible... but you won't get -0.3333.. in this case
NO!!! you have two use the equations which are available to you
What would it be @Rosh007 because thats what i got, am i doing it wrong then??
ur right @JessNicole
Try using substitution and see if you got the same as me. (:
@jazy you made a mistake here Solve for x in the first equation. x + y = 4 Subtract y. x = 4 - y Substitute the value of x into the second equation. Solve for y. 2(4 - y) = 5 ----- mistake
be careful @jazy 2(4 - y) = 5 ???? the right is 2(4 - y) - y= 5
@jazy THANK YOU!!! it makes sence but @Rosh007 how is it a mistake?
be careful @jazy the mistake at 2(4 - y) = 5 ???? the right is 2(4 - y) - y= 5
@JessNicole please look gerryliyana's reply
Ohh okayy, i see now soo, it'd be Distribute 8-y=5?? @Rosh007 and @jazy ??
jazzy missed one y there
@gerryliyana Thank youuuu!!:) for catching that mistake, i fixed it on my paper!
I prefer substitution. x + y = 4 2x - y = 5 Solve for x in the first equation. x + y = 4 Subtract y. x = 4 - y Substitute the value of x into the second equation. Solve for y. 2(4 - y) - y = 5 Distribute. 8 - 2y - y= 5 Subtract 8. -2y - y = -3 -3y = -3 Divide both sides by -3. y = 1 Now plug in the value of y(1) into any equation to solve for x. x + y = 4 x + 1 = 4 Subtract 1 x = 3 ---------------------------------- So x = 3 and y = 1
@gerryliyana What would it be then?
2(4 - y) - y= 5 8 - 3y = 5
2(4 - y) - y= 5 8 - 3y = 5
Thank you catching that mistake! (:
yes you got it jazzy.. but a very simpl method is there
@JessNicole 2(4 - y) - y= 5 8 - 3y = 5
@jazy @Rosh007 @gerryliyana THANK YOUUUUUUUUU!! SO MUCH EVERYONE!!:D .. I'd give all of you guys each a medal if i could!!
sice answer is already wrote here( which I don't like to do write directly) it is for you to know that there is a simple method than this
@JessNicole ur welcome..., happy to help u :)
@Rosh007 There's an easier way ? cause you can teach it to me ..this stuff is hard for me, i'm always confused.
actually it is derivd from the method mentioned here.. It is actually a special case of this method.. it is applicabl here since in one equation +y and in other equation -y is there actually the problem is simple x+y=4 2x-y=5 |dw:1353003234368:dw| so when we add both equation (LHS with LHS and RHS with RHS) you get 3x =9 which can be simplified quickly and reach the answer fast
actually the problem is simple x+y=4 2x-y=5 add x+y+2x-y = 5+4 3x+0 = 9 3x =9 if you substitute the value of x in equn 1 you get th value of y....
@Rosh007, yess! i understood perfectly. It is much simpler!..Thank you very much. I really appreciate it.!:)
Welcome...But remember it is a special case ;) all the best
Ha ha okay, thank youagain !:p